Single nucleotide polymorphisms at the microRNA-binding site of KIAA0423 are associated with colorectal cancer - Yue Zhao; Huichai Yang; Xiaoxu Luo; Cuiju Wang; Ruixing Zhang; Zhanjun Guo (Biotechnology & Biotechnological Equipment, 2016)
MicroRNAs (miRNAs) binding to the 3′-untranslated regions (3′UTRs) of messenger RNAs to mediate translation and thereby regulate cell differentiation, apoptosis and tumorigenesis. Single nucleotide polymorphisms (SNPs) in the 3′UTRs of genes would alter the binding affinity between targeted genes and miRNA so as to change individual gene expression. We genotyped miRNA-binding-site SNPs in a case-control study with sporadic colorectal cancer (CRC) patients to identify CRC risk associated SNPs. Five miRNA-binding-site SNPs located in the 3′UTR of KRT81 (rs3660), RYR3 (rs1044129), KIAA0423 (rs1053667), C14orf101 (rs4901706) and GOLGA7 (rs11337) were genotyped in CRC patients, using polymerase chain reaction–ligase detection reaction (PCR–LDR) methods. Renilla luciferase reporter assays were used to measure the binding affinity between miRNA and the targeted gene. The χ2 test was used to study the association between carriership of miRNA-binding-site SNPs and CRC risk. The SNP of rs1053667 located in the 3’UTR of KIAA0423 gene was identified to be associated to CRC cancer risk, with the TT allele being associated with a 2.030-fold increased risk for CRC than that associated with the C/T+C/C genotype (odds ratio of 2.030; 95% confidence interval of 1.314–3.136; P < 0.01). The reduced Renilla luciferase activity of rs1053667 TT type comparing with that of CC genotype also demonstrated the different binding affinity of rs1053667 SNPs to the corresponding miRNA. The miRNA-binding-site SNP of rs1053667 in the KIAA0423 gene could be associated with risk of CRC.